Pemanfaatan Media Pembelajaran Papan Ular Tangga Cerdas untuk Meningkatkan Motivasi Belajar Matematika Siswa SD Negeri 3 Masbagik Selatan - Burhanuddin; Agisna Bil’ulum; Aulia Fitriana; Nurhaeni Nurhaeni; Raniyarti Raniyarti; Susi Sulastri; Yusril Ihwan (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This study aims to describe the use of intelligent snakes and ladders board learning media in increasing students' motivation to learn mathematics at SD Negeri 3 Masbagik Selatan. The background of this study is based on the low interest and motivation of students in learning numeracy due to the minimal use of innovative learning media by teachers. Through the Teaching Assistance Program (AM) of Hamzanwadi University in 2025, students were directly involved in the design process, socialization, and implementation of the intelligent snakes and ladders board media. This study used a qualitative method with a field study approach, including observation, interviews, and documentation. The results showed that the use of intelligent snakes and ladders board media was able to increase students' involvement and motivation to learn mathematics. Students became more active, enthusiastic, and easily understood the material on fractional arithmetic operations. This media was also well received by teachers and students, and provided a new alternative in a creative and enjoyable learning process. This experience is expected to inspire schools to continue developing innovative learning media to support the quality of education.